Cyclosporine improves remyelination in diabetic rats submitted to a gliotoxic demyelinating model in the brainstem - Bondan, Eduardo Fernandes; Monteiro Martins, Maria De Fatima (Wiley-Blackwell, 2013)
The use of cyclosporine (CsA) has shown to induce an increase in density of oligodendrocytes near remyelinating areas following the injection of ethidium bromide (EB), a demyelinating agent, in the rat brainstem. It is also known that diabetes mellitus was capable of delaying remyelination by both oligodendrocytes and Schwann cells in this gliotoxic model. This study was designed to assess whether CsA had the capacity to improve remyelination in streptozotocin-induced (50 mg/kg, intraperitoneal route) diabetic rats. Diabetic Wistar rats were divided in different groups receiving 10 microlitres of 0.1% EB or 0.9% saline solution into the cisterna pontis and were treated or not with CsA. During 7 days and, thereafter, three times a week, 10 mg/kg/day of CsA were given by intraperitoneal route. The rats were euthanized from 7 to 31 days after EB or saline injection and brainstem sections were collected and processed for light and transmission electron microscopy studies. Results from different groups were compared by using a semi-quantitative method developed for documenting the extent and nature of remyelination in semithin sections following gliotoxic lesions. Results showed that CsA administration to diabetic rats after EB injection stimulate both oligodendroglial and Schwann cell remyelination (mean remyelination scores of 3.15 +/- 0.5 for oligodendrocytes and 1.36 +/- 0.58 for Schwann cells) compared to untreated animals (2.52 +/- 0.71 for oligodendrocytes and 0.73 +/- 0.47 for Schwann cells, respectively). CsA given to diabetic rats was capable of reversing some of the deleterial effects of diabetes on remyelination. Microsc. Res. Tech. 76:714-722, 2013. (c) 2013 Wiley Periodicals, Inc.
Keywords: cyclosporine; diabetes mellitus; oligodendrocytes; remyelination; Schwann cells